Total electron content studies of the ionosphere - Klobuchar, John A.; Air Force Cambridge Research Laboratories (U.S.) (L.G. Hanscom Field, Bedford, Massachusetts : Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1973)
Radio waves that pass through the earth's ionosphere travel more slowly than their free space velocity due to the group path delay of the ionosphere. This group path delay, directly proportional to the total electron content of the ionosphere, can be an important source of error to VHF, UHF and L-band satellite detection radars and satellite navigation systems. In this report, the current state of knowledge of ionospheric total electron content is outlined, with special emphasis placed on the North Atlantic region of the world due to NATO special requirements of this region. A numerical model of total electron content, valid over the European continent under certain conditions, is presented for systems engineering use for an average background total electron content correction. Typical values of total electron content are also given at various locations in the high, middle, and equatorial latitudes. If the results presented here seem incomplete, it is only because the state of knowledge of the total electron content parameter is still incomplete. With more observational data being taken at many locations, an over-all satisfactory picture of the world-wide behavior of this important parameter is beginning to emerge. (Author). "Ionospheric Physics Laboratory Project 4643." AD0762481 (from http://www.dtic.mil). "1 February 1973." Includes bibliographical references. Radio waves that pass through the earth's ionosphere travel more slowly than their free space velocity due to the group path delay of the ionosphere. This group path delay, directly proportional to the total electron content of the ionosphere, can be an important source of error to VHF, UHF and L-band satellite detection radars and satellite navigation systems. In this report, the current state of knowledge of ionospheric total electron content is outlined, with special emphasis placed on the North Atlantic region of the world due to NATO special requirements of this region. A numerical model of total electron content, valid over the European continent under certain conditions, is presented for systems engineering use for an average background total electron content correction. Typical values of total electron content are also given at various locations in the high, middle, and equatorial latitudes. If the results presented here seem incomplete, it is only because the state of knowledge of the total electron content parameter is still incomplete. With more observational data being taken at many locations, an over-all satisfactory picture of the world-wide behavior of this important parameter is beginning to emerge. (Author). Mode of access: Internet.